Contemporary use of glycoprotein IIb/IIIa inhibitors - Kristensen, Steen Dalby; Würtz, Morten; Grove, Erik Lerkevang; Caterina, Raffaele De; Huber, Kurt; Moliterno, David J.; Neumann, Franz-Josef (Thrombosis and Haemostasis, 2012)
Platelet glycoprotein IIb/IIIa inhibitors (GPI) are antithrombotic agents preventing the binding of fibrinogen to GP IIb/IIIa receptors. Thus, GPI interfere with interplatelet bridging mediated by fibrinogen. Currently, three generic GPI with different antithrombotic properties are available for intravenous administration: abciximab, eptifibatide, and tirofiban. The development of oral GPI was abandoned, whereas intravenous GPI were introduced in various clinical settings during the 1990s, yielding substantial benefit in the treatment of acute coronary syndromes, particularly during percutaneous coronary interventions. Results of the many randomised trials evidenced the efficacy of this drug class, though these trials were conducted prior to the emergence of modern oral antiplatelet therapy with efficient P2Y12 inhibitors. Subsequent trials failed to consolidate the strongly favourable impression of GPI, and indications for their use have been more restricted in recent years. Nonetheless, GPI may still be beneficial during coronary interventions among high-risk patients including acute ST-elevation and non-ST-elevation myocardial infarctions, particularly in the absence of adequate pretreatment with oral antiplatelet drugs or when direct thrombin inhibitors are not utilised. Intracoronary GPI administration has been suggested as adjunctive therapy during primary percutaneous coronary intervention, and the results of larger ongoing trials are expected to elucidate its clinical potential. The present review outlines the key milestones of GPI development and provides an up-to-date overview of the clinical applicability of these drugs in the era of refined coronary stenting, potent antithrombotic drugs, and novel thrombin inhibiting agents.
Keywords: Abciximab; acute coronary syndrome; antiplatelet agents; glycoprotein IIb/IIIa inhibitors; percutaneous coronary intervention